ANALISIS MASALAH RENDAHNYA HASIL BELAJAR SISWA INDONESIA MENGGUNAKAN TEORI HAKEKAT HASIL BELAJAR BLOOM - Meilinda Khasanah; M. Mamduh Winangun; Sri Usodoningtyas (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Low learning outcomes of Indonesian students have become a crucial national education issue, evidenced by PISA 2022 scores below the OECD average (detik.com, 2025). This library research analyzes two main problem formulations based on national media reports and international journals: (1) 75% of students fail to reach PISA level 2 reading literacy, and (2) 82% struggle to apply numeracy in real life. Solutions are offered through Bloom's Theory of Learning Outcomes (Revised Bloom's Taxonomy 2001) which classifies learning objectives into six cognitive levels: remembering, understanding, applying, analyzing, evaluating, and creating. Analysis shows this tiered approach can improve literacy by 28% and numeracy by 32% through problem-based learning and tiered formative assessment.